Advanced adrenocortical carcinoma successfully treated with gemcitabine plus capecitabine as second‐line chemotherapy. Issue 6 (30th August 2020) - Yamamoto, Akinaru; Nakai, Yasutomo; Oka, Toshiki; Kanaki, Tomohiro; Yamamoto, Yoshiyuki; Nagahara, Akira; Nakayama, Masashi; Kakimoto, Ken‐ichi; Nishimura, Kazuo
Abstract : Introduction: Adrenocortical carcinoma is a rare malignant tumor with an unfavorable prognosis in the advanced stage for which second‐/third‐line chemotherapy is not well established. Case presentation: A 34‐year‐old woman was referred to our institution for left adrenal tumor with multiple liver metastases and tumor thrombus extending to the inferior vena cava. According to her clinical diagnosis of adrenocortical carcinoma (T4N0M1, European Network for the Study of Adrenal Tumors stage IV), we resected the left adrenal tumor and tumor thrombus. Pathological examination confirmed the adrenocortical carcinoma diagnosis. After four courses of etoposide, doxorubicin, cisplatin, and mitotane therapy, the liver metastases progressed, and we started gemcitabine, capecitabine, and mitotane therapy as second‐line chemotherapy. After 7 months, significant shrinkage of the liver metastases was observed, and they remained stable over 16 months. Conclusion: We reported a case of advanced adrenocortical carcinoma with significant shrinkage of liver metastases following gemcitabine, capecitabine, and mitotane therapy, with the effect maintained over 16 months.